Resilient Dams for Malaysia: A Risk-Informed Decision-Making-Based Approach - Sidek L.M.; Ahmad S.A.; Yunus A.M.; Saman D.H.; Basri H.; Yusof N.M.; Torres A.M.; Rohaizi M.S.; Azizi A.S.M. (Springer Science and Business Media Deutschland GmbH, 2024)
Catastrophic dam failures result in significant loss of lives and immense property damage worldwide. The causes of dam failures are primarily attributed to three major triggers: climate change, ageing dams, and cyber threats. Understanding the correlation between these factors is vital to provide a comprehensive solution in the dam safety sector. The authors propose a new method called risk-informed decision-making (RIDM). RIDM evaluates the likelihood of loading scenarios, potential failure modes, and economic and social consequences to compute the risks for dams on the Perak River. The study aims to identify probable failure modes, evaluate consequences, and develop mitigation measures and conceptual designs. The study will include several stages, such as gap analysis and dam safety evaluation, followed by a Risk-Based Screening Tool to obtain the initial risk results. Failure mode identification will be made through detailed technical visits and participatory working sessions involving key staff in maintenance, operation, and safety management. Developing a quantitative risk model will quantify the risk according to the specified fundamental failure modes. The final risk results will recommend and evaluate mitigation measures to ensure a resilient dam for a safe community. Additionally, a secure dam safety database system will be developed as an efficient tool to manage various data types to assist the dam owner in decision-making. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.